2004
DOI: 10.1158/1078-0432.ccr-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Micrometastatic Disease and Monitoring of Perioperative Tumor Cell Dissemination in Primary Operable Breast Cancer Patients Using Real-Time Quantitative Reverse Transcription-PCR

Abstract: Purpose: We previously found a statistically significant number of cytokeratin 19 (CK19)؉ cells in peripheral blood (PB) of stage IV breast cancer (BC) patients compared with those of healthy volunteers, using a quantitative real-time reverse transcription-PCR. We aimed to apply the technique on bone marrow (BM) of primary operable BC patients. Pre-and postoperative PB samples of these patients were further analyzed to investigate possible shedding of CK19؉ cells during the operation.Experimental Design: In 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
1
12
1
3
Order By: Relevance
“…Nevertheless, the high concordance observed between CTC and DTC detection in our study favours the hypothesis that there is a continuous circulation and exchange of epithelial cells between bone marrow and peripheral blood. The high detection rate of occult tumour cells in both peripheral blood and bone marrow observed in the current study is in overt contrast with previous studies reporting low detection rates using immunocytochemical assays (Ismail et al, 2004;Pierga et al, 2004;Muller et al, 2005;Wiedswang et al, 2006;Benoy et al, 2006) and should be attributed to the high sensitivity and specificity of the quantitative RT-PCR assay used for the detection of minimal residual disease . Moreover, it is interesting to note that only 10% of 1767 patients with early disease had more than one CTC per 23 ml of peripheral blood when tested with the new automated Cell Search System (Rack et al, 2007(Rack et al, , 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the high concordance observed between CTC and DTC detection in our study favours the hypothesis that there is a continuous circulation and exchange of epithelial cells between bone marrow and peripheral blood. The high detection rate of occult tumour cells in both peripheral blood and bone marrow observed in the current study is in overt contrast with previous studies reporting low detection rates using immunocytochemical assays (Ismail et al, 2004;Pierga et al, 2004;Muller et al, 2005;Wiedswang et al, 2006;Benoy et al, 2006) and should be attributed to the high sensitivity and specificity of the quantitative RT-PCR assay used for the detection of minimal residual disease . Moreover, it is interesting to note that only 10% of 1767 patients with early disease had more than one CTC per 23 ml of peripheral blood when tested with the new automated Cell Search System (Rack et al, 2007(Rack et al, , 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, Schoenfeld et al (1997) have reported that the concordance between blood and bone marrow samples for occult tumour cell detection was only 6% by immunocytochemistry and 27% by RT-PCR. The lack of a complete overlap between the presence of CK-19 mRNA-positive CTCs and DTCs either before (Ismail et al, 2004;Pierga et al, 2004;Muller et al, 2005;Wiedswang et al, 2006) or after chemotherapy (Slade et al, 2009) could be related to the fact that occult tumour cells are rare events and therefore their evaluation is greatly influenced by sampling variability. In addition, it has been suggested that blood represents a temporary compartment for disseminated cells (Muller et al, 2005), whereas only a subpopulation of CTCs can settle in distant organs such as the bone marrow (Muller et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with several other studies (Schoenfeld et al, 1997;Slade et al, 1999;Berois et al, 2000;Stathopoulou et al, 2002;Ismail et al, 2004;Pierga et al, 2004), all of whom demonstrate that BM is more likely to be positive than PB for the presence of DEC (Table 4). Cancer cells may be intermittently shed into the bloodstream, which could result in a sampling error if a single-point sampling is evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, tumor cell dissemination is non-linear, and marker gene expression may vary between a primary tumor and its metastasis [19,20] . Therefore, multiple marker genes have been recently applied to improve the detection sensitivity in this cancer patients [21][22][23] , and single gene quantification at multiple time points has also been proposed for exploring the micrometastatic characteristic [24,25] . However, in colorectal cancer patients this method has not been used due to lack of effective marker genes combination applicable in PB.…”
Section: Introductionmentioning
confidence: 99%